2014
DOI: 10.1177/1545968314542617
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the BDNF Gene Interacts With Age to Predict Mortality in a Prospective, Longitudinal Cohort with Severe TBI

Abstract: Background Mortality predictions following traumatic brain injury (TBI) may be improved by including genetic risk in addition to traditional prognostic variables. One promising target is the gene coding for brain-derived neurotrophic factor (BDNF), a ubiquitous neurotrophin important for neuronal survival and neurogenesis. Objective We hypothesized the addition of BDNF genetic variation would improve mortality prediction models and that BDNF Met-carriers (rs6265) and C-carriers (rs7124442) would have the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 69 publications
4
78
0
Order By: Relevance
“…However, it is also possible the mechanism of rs6279's impact on cognition post-TBI may be diminished at 12 months. The temporal dynamics of these DRD2 associations is consistent with other studies from our group that demonstrate transient genetic outcome associations across recovery post-TBI 64,65 . Domain specific analysis supports slightly different roles for each SNP in overall cognitive recovery.…”
Section: Discussionsupporting
confidence: 89%
“…However, it is also possible the mechanism of rs6279's impact on cognition post-TBI may be diminished at 12 months. The temporal dynamics of these DRD2 associations is consistent with other studies from our group that demonstrate transient genetic outcome associations across recovery post-TBI 64,65 . Domain specific analysis supports slightly different roles for each SNP in overall cognitive recovery.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have shown that genetic variation is associated with outcomes and conditions following TBI (Hoh et al, 2010;Weaver et al, 2012;Wagner et al, 2012;Garringer et al, 2013;Diamond et al, 2014;Failla et al, 2014). Of note, an IL-6 polymorphism (À174 G/C) has been reported as associated with mortality after severe TBI (Dalla Libera et al, 2011) and the development of Alzheimer's disease in non-TBI populations (Qi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Age 2628 and experimental TBI 29 can shift regional balances in BDNF receptor ratios from pro-survival to pro-apoptotic. In fact, our previous work demonstrated age and injury specific associations with the BDNF gene and mortality post-TBI 10 . We examined two single nucleotide polymorphisms (SNP) within BDNF , rs6265, with reduced activity-dependent secretion of BDNF 30 , and rs7124442, which impairs neuronal BDNF mRNA trafficking 31 .…”
Section: Introductionmentioning
confidence: 86%
“…Consistent with previous work 10 , mortality was evaluated over two time-epochs, 0-7d post-injury ( acute ) and 8d-365d post-injury ( post-acute ), and then across the entire recovery span of 0-365. For 0-7d, survivorship was right censored at 7d post-injury.…”
Section: Methodsmentioning
confidence: 99%